Perceptions of unprofessional behavior in the clinical workplace among healthcare staff - Marji Qayyadh Alruwaili; Abbas Abdullah Ali Alhamed; Latifa Nawaf al Rashedi; Mohammad Misfer Alkhathami; Abeer Awad Suwaylim Alanazi; Fahad Alanazi; Maram Alabbasi; Myada Ali Alhadab (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Professionalism among healthcare providers is essential to fostering trust, ensuring patient safety, and maintaining effective communication within healthcare teams. Despite general professionalism among providers, unprofessional behavior—such as exclusion, blaming, and lack of responsiveness—persists, with negative impacts on clinical outcomes and provider well-being. This study investigates the prevalence and types of unprofessional behaviors within an academic medical center, analyzing how these behaviors vary by role, gender, and department. Methods: This cross-sectional study surveyed attending physicians, residents, and advanced practice providers (APPs) at a tertiary academic medical center. Participants were surveyed on the frequency and types of unprofessional behaviors experienced or witnessed, using an adapted workplace behavior survey based on Joint Commission standards. Surveys were distributed during mandatory professionalism training sessions with results analyzed using ordinal and negative binomial regression to assess associations between role, gender, and behavior frequency. Results: Among 388 respondents, 63% reported experiencing unprofessional behavior monthly or more frequently, with behaviors like non-responsiveness (44.3%) and exclusion from decision-making (43.0%) most commonly reported. Residents were more likely to encounter unprofessional behavior than attending physicians (OR 2.25, p < 0.001), and APPs frequently reported dismissive behavior (OR 2.44, p < 0.05). Female respondents faced higher rates of discrimination (OR 2.52, p < 0.01) than males. Cross-department interactions were a significant source of unprofessional behavior, with nurses, other residents, and attending physicians outside one’s department identified as common sources. Discussion: The findings highlight the need for targeted interventions to address unprofessional behaviors within specific roles and interdepartmental interactions. Frequent unprofessional conduct by and toward residents and APPs underscores the importance of tailored training programs and organizational support systems. Further research is warranted to explore interventions that foster professionalism and reduce the occurrence of disruptive behaviors across healthcare teams.